Pattern, Determinants and Dynamics of Austrian Service Exports - A Firmlevel Analysis - Yvonne Wolfmayr; Elisabeth Christen; Michael Pfaffermayr (FIW - Research Centre International Economics, 2013)
Most firm-level research on the characteristics and strategies of globalized firms focuses on manufacturing industries while firm-level evidence on trade in services is still rare and has just recently begun to emerge. This study uses an unique dataset of Austrian service exporting firms over a four-year period to add to this literature. We show that service export participation is very low and highly concentrated among a few firms and that service exporters are on average larger and more productive than non-exporters. We also find that firm productivity increases with the number of export markets served. The detailed analysis on the export premium suggests the self-selection of firms as well as learning effects from exporting for export starters. The dynamic analysis reveals that the rate of export exits is high for export starters in the first year of exporting, especially for firms of small size. Movements into and out of exporting are however less frequent than moving in and out of individual markets. Entry and exit of markets (extensive margin) is an important component of overall export flows, especially for less popular markets, overall, however the intensive margin of trade contributes most. Analysis based on a Heckman sample selection specification including firm characteristics as well as the standard gravity variables on geographical characteristics of destination markets confirm this finding. In particular, distance to the destination market, firm productivity as well as destination market characteristics (market size, policy environment) significantly influence the probability of exporting but even more so the volume of service trade flows. Results from the counterfactual analysis suggest that export market growth and policy reforms produce the relative strongest impact on the entry into new markets. Hence, this decomposition of overall export growth into contributions attributable to the extensive and intensive margin allow for new insights for economic policy.
Keywords: C12; C21; D22; F14; L80; C15; L20; 330; service trade; firm-level evidence; export productivity premium; intensive and extensive margin of trade; gravity model; firm heterogeneity; sample selection; market coverage